Analysis of Social Conflict in Sangihe Island Coverage BBC News Indonesia - Deden Wijaya; Nawawi Nawawi (Budapest International Research and Critics University, 2022)
Conflict management is the process by which a conflicting party or third party develops a conflict strategy and implements it to control the conflict to produce the desired solution. This study aims to determine the causes or factors of conflict in BBC New Indonesia's coverage of Sangihe Island. This study uses non-participant observation, where researchers observe research subjects without direct participation. This observation is done by watching the film and reading the contents of the film. Documentary reporting that gold mines on Sangihe Island threaten endemic forests and endangered birds - BBC News Indonesia caught the attention of Indonesians because the video has been viewed more than 200,000 times on their YouTube channel. This shows that the topics presented in the video are interesting and need to be informed to a wide audience. The rejection of PT TMS by the Sangihe community was caused by several factors, among which the Sangihe community did not agree with PT TMS because they wanted to protect and preserve the nature of Sangihe's return.